2015
DOI: 10.1038/srep14694
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mosquito FREP1 with a fungal metabolite blocks malaria transmission

Abstract: Inhibiting Plasmodium development in mosquitoes will block malaria transmission. Fibrinogen-related protein 1 (FREP1) is critical for parasite infection in Anopheles gambiae and facilitates Plasmodium invasion in mosquitoes through interacting with gametocytes and ookinetes. To test the hypothesis that small molecules that disrupt this interaction will prevent parasites from infecting mosquitoes, we developed an ELISA-based method to screen a fungal extract library. We obtained a candidate fungal extract of As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…Fortunately, we successfully cultured two wild malaria isolates under laboratory conditions. Using the IFA method as we described previously 16 , 17 , results clearly showed that FBN30 co-localized with wild type P. falciparum ookinetes (Fig. 3c ).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Fortunately, we successfully cultured two wild malaria isolates under laboratory conditions. Using the IFA method as we described previously 16 , 17 , results clearly showed that FBN30 co-localized with wild type P. falciparum ookinetes (Fig. 3c ).…”
Section: Resultssupporting
confidence: 60%
“…gambiae to clinically circulating P. falciparum . Variations in length and composition of signal peptide sequences that change secretory efficiency of a mature protein have been reported in other organisms including humans 17 , 26 , 27 . For example, the insertion/deletion polymorphisms of apolipoprotein B within its signal peptide are associated with plasma glucose levels in Europeans and Mexican Americans 28 .…”
Section: Discussionmentioning
confidence: 85%
“…Standard membrane feeding assays (SMFA) were performed as the previous reports [12, 24]. About 30 μL anti-sera were mixed with 330 μL cultured P. falciparum and fed 3-5-day-old female An.…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of these interventions is however continually challenged and threatened by the evolution of insecticide (3, 4) and drug resistances (5, 6). To overcome resistance issues, the re-emergence of the concept of malaria transmission-blocking strategies (710) has boosted the research efforts to find molecules (11, 12) or microorganisms (1316) able to inhibit the transmission of parasites or to disturb the life cycle of Plasmodium in the mosquito vector. Understanding the fundamental processes of parasite transmission from human to mosquito vector is therefore essential to this aim.…”
Section: Introductionmentioning
confidence: 99%